EVALUATION ON AGGREGATION RISK RATE FOR DEFUZZIFICATION IN FUZZY SETS - Kayalvizhi, S.; *, Gunasekar; *, Thenmozhi (IJRDO -Journal of Computer Science Engineering, 2016)
The main aim of the proposed method is to present that the defuzzification process using median rule is not similar to the process that follows classical centroid rule. The classical centroid rule uses either triangular or trapezoid moments. The triangular or trapezoid is taken with isosceles principle and defuzzification with such median principle is proved with reduced error tolerance.